ON SOME LINGUISTIC FEATURES OF COMMUNICATION IN DIPLOMACY - Ghukasyan, Varduhi (Armenian Folia Anglistika, 2024)
The article provides an insight into diplomatic language through the discussion of the language choices in James Cleverly’s and Annalena Baerbock’s speeches. The diplomats’ main weapon is their language. Diplomats speak a lot and give little information. Diplomatic communication is based on the use of various strategies and tactics. The most common ones include: the strategy of “ambiguity”, the strategy of “mitigation”, the tactics of euphemistic substitution, the subjectivity of assessment and communicative tolerance. The main purpose of these strategies is to maintain one’s own interests and create a positive tone of communication. The aim of the study and the specifics of the data chosen determine the choice of the following research methods in the study of diplomatic discourse: the method of direct observation of the material, followed by analysis and generalization of the results, contextual-interpretive and content analysis methods, as well as methods of linguistic description.
Keywords: diplomatic discourse; diplomatic communication; ambiguity and mitigation strategies; international relations